VOPO4⋅2H2O: Large-Scale Synthesis and Zinc-Ion Storage Application - Zhang, Xianghua; Yang, Dan; Liu, Weiling; Rui, Xianhong (Frontiers in Energy Research, 2020)
Rechargeable aqueous zinc ion batteries (ZIBs) have attracted increasingly solicitude in the application of large-scale electrochemical energy storage system (EES) as a result of their low-price, high security and environment-friendly. The synthesis of mass-produced electrode materials and the exploration of their potential electrochemical properties are essential steps to achieve superior large-scale EES. In this work, the large-scale preparation of vanadium oxyphosphate hydrate (VOPO4⋅2H2O) cathode material with impressively zinc storage ability is successfully demonstrated. Specially, it exhibits a high specific capacity of 165 mAh g–1 at 0.05 A g–1, and prominent rate property (90 and 75 mAh g–1 at 2 and 5 A g–1, respectively), as well as stable cyclability of 76% after 1000 cycles under a high current density of 5 A g–1 within the voltage window of 0.4–1.6 V (versus Zn2+/Zn). Moreover, the VOPO4⋅2H2O not only spreads superiority in electrochemical performance, but also shows the advantages of scalable production based on simple controllable adjustment in synthesis, which is expected to exhibit great development potential in the field of large-scale EES application.